(3MGOi GdbdhH Edi dbGA GdeMHhHs - (3CHh YHO Gddg eMeO Hf GdedGM GdTGPdj,J (B797 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf GdfahS eaWhQI Ydi cQGgg GdeDdeGJ hdeG cGf GdehJ GYXe eUGjH GdOfjG aGfJgRJ GdaQUi HGdGNJUGQ hGdGLeGd hPcQJ ai gPG GdJYdjb cdjGJ efHgg s
(3BNQgG (B:s
(3hGHSW jG MHjHi Gedc GdMSf ai QMeI Gdgd JYGdi aEfc dGJNjH eY hLhO GdTaGYGJ ef GdGfHjGA hGdeQSdjf s
(3fSNI NRGFfjIs
(3Ydjg Jedjc dCHi HcQ Hf bWdhHZG HJGQjN YGe SJ hKeGfeGFIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B623s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG RNGQa s
Keywords: (3GdJUha hGdBOGH GdTQYjIs